Assessment of Raktasarata: Conversion of Theory into Practical Approach - Bhawsar, Priyanka; Nampalliwar, Amit R (International Research Journal of Ayurveda & Yoga, 2024)
Raktasarata is assessed with the reference from ancient Ayurvedic books like Charaka, Sushrutaand Vaghbhata. Detailed proforma of raktasara is prepared. Characters of raktasarata described by Charaka and Sushruta have taken into consideration. The terms Sukha, Medha, Manaswita, Uddhata, Anatibalam, Ushnasahishnutvam are tried to explain and proforma is prepared to rule out these mental characters. Characters of Raktasara person described by Charaka and Sushruta belong to Raktapravarasara persons. Characteristics of Raktamadhyamsara And Raktaasara are not described in texts. If the characters of sara are absent then dhatu is said to be Asara while some characters of Raktasara are observed in Raktamadhyamsara persons. In ancient days, due to unavailability of devices, study of dhatu was done by examining external structures of body.